2019
DOI: 10.1097/olq.0000000000001020
|View full text |Cite
|
Sign up to set email alerts
|

Sex Worker Community-led Interventions Interrupt Sexually Transmitted Infection/Human Immunodeficiency Virus Transmission and Improve Human Immunodeficiency Virus Cascade Outcomes: A Program Review from South India

Abstract: A review of a community-led sex worker program in 2 districts of South India that has achieved near elimination of curable sexually transmitted infections and optimal human immunodeficiency virus cascade outcomes. Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…These positive programme outcomes align with evidence from other countries regarding sex worker-led collectives' ability to reduce STI and HIV infection rates (e.g. Reza-Paul et al 2019). The organisation's success rate makes the staff feel proud and increasingly in control of the biomedical dimensions of HIV.…”
Section: Resultssupporting
confidence: 70%
“…These positive programme outcomes align with evidence from other countries regarding sex worker-led collectives' ability to reduce STI and HIV infection rates (e.g. Reza-Paul et al 2019). The organisation's success rate makes the staff feel proud and increasingly in control of the biomedical dimensions of HIV.…”
Section: Resultssupporting
confidence: 70%
“…Our qualitative research with 30 female sex workers in Kisumu, Kenya, conducted prior to the COVID-19 pandemic, found that economic assistance during illness and for funeral expenses and release after arrests were common, as were other forms of support, including protection from violence by clients and the police, social support, and information-sharing [ 27 ]. Research into the role of mutual aid practices and networks among female sex workers during the pandemic may yield insight to strengthen interventions that leverage female sex workers' support systems [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…43 Another communityled intervention among sex workers in Karnataka, India, reported significant reductions in the prevalence of syphilis (45.4%, from 24.9% to 13.6%), gonorrhoea (83.3%, from 5.4% to 0.9%) and chlamydia (63.0%, from 10.8% to 4.0%) from the start of the intervention in 2004 until 2009 -with more recent routine clinical data suggesting near elimination of symptomatic cases of sexually transmitted infections. 22,23,25 Increasing condom use and statistically significant declines in sexually transmitted infections and HIV were reported in surveys from other districts in Karnataka from 2004 to 2011. 24,25 Large reductions in syphilis and HIV prevalence were also reported in pregnant women over the same period.…”
Section: Policy and Practicementioning
confidence: 97%
“…24,25 Large reductions in syphilis and HIV prevalence were also reported in pregnant women over the same period. 23,44 Among the remaining seven countries in the South-East Asia Region, routine surveillance of sexually trans-mitted infections is neither complete nor reliable enough to assess trends and few studies are reported in the literature. Where declines in sexually transmitted infections have been documented in a few specific locations, these reductions are linked to programmes that have increased condom use in sex work while also improving clinical services for sexually transmitted infections, or are associated with specific interventions for sexually transmitted infections such as periodic presumptive treatment.…”
Section: Policy and Practicementioning
confidence: 99%